Student Management to Improve The Quality of Education in Effective Schools (A Case Study at MAN Insan Cendekia Serpong) - Muawanah Muawanah (Didaktika Religia, 2021)
This article aims to explain the planning, development, and evaluation of students in effective schools at MAN Insan Cendekia Serpong Tangerang Banten. Student management has a strategic position in developing the quality of education. Better student management will increase the achievement of students. The author acts as a key instrument in data collection, because this research used a qualitative approach with a type of case study. The author explores data based on the archive system and the effectiveness of decision making, then collects, explains, and analyzes it. This article concludes that the student planning at MAN Insan Cendekia starts with an online new student registration system. Selection is carried out in a transparent and accountable manner by involving independent parties from outside. The selection stages include administrative, scholastic talent, academic, and medical examination selection. The development of students at MAN Insan Cendekia is carried out by involving the active role of schools, mosques and dormitories. These three development centers work together and holistically to achieve the school's vision. The development of students there includes disciplinary, academic and non-academic aspects. Meanwhile, the evaluation of students at MAN Insan Cendekia is implemented in a transparent, accountable, continuous, and comprehensive manner with high standards. In summary, the evaluations carried out are daily tests, midterm exams, final semester exams, and national exams. However, evaluation focuses more on the process, assuming that if the process is good, then the results will also be of high quality.